The role of Interleukin-10 in Helicobacter pylori infection - Zakaria, Zuraihan (2010)
Background & Aims: Helicobacter pylori (H. pylori) chronic infection is the major cause of peptic ulceration and gastric cancer. Strains with the cag pathogenicity island (cagPaI) are more strongly associated with disease. In earlier studies, higher levels of interleukin-10 (IL-10) were found in human gastric biopsies with the highest H. pylori colonisation density grading. In the current study, experiments were performed to determine if this effect could be replicated in vitro using human gastric epithelial cell lines. Although IL-10 is abundant in the gastric mucosa, the nature of its interaction with the epithelium is unknown. IL-10 receptor (IL-10R) expression on gastric epithelial cells was therefore investigated.